Analisis Efisiensi Teknis Usaha tani Tebu Di Desa Arjosari Bagian Timur (Studi Kasus Di Desa Arjosari Bagian Timur, Kecamatan Kalipare, Kabupaten Malang) - Rosari Rahayuningtyas, Maria; Puri Nurani, Maria; Perwita Rahmanti Ignatia, Sari (Fakultas Pertanian, 2024)
Sugarcane plantations played an important role in increased value-added in the economy. Sugarcane is used as a key ingredient in sugar production. High consumption has not offset the production of sugar. Production can meet consumption by performing technical efficiency of usaha tani. This study is aimed at identifying the impact of the use of sugarcane production factors and the technical efficiency of the use of sugarcane production factors. The implementation of this study is in the village of Arjosari in the east, Calypso district, unfortunate district. The study population is 35 respondents in sugarcane growers. Sample strain strain is 32 respondents. The methods used in data collection are observation, interviews, and questionnaires. Analysis used is linear regression using f-test, t-test, and technical efficiency. Results obtained in this study indicate that in a simultaneous free variable (x) has an effect on bound variables (y). Those that have partial effects are manure (x3), zec fertilizer (x4), and labor (x7). Other such variables as land area (x1), seeds (x2), fertilizer phonska (x5) and drops or molasses (x6) have no effect on sugarcane production. Technical efficiency is known for the value of constants obtained in the production function of the cobb douglass stochastic frontier. Unavailable translation service. Subscribe now to enjoy professional translation